3D printed pharmaceuticals and medical devices: an interview with Álvaro Goyanes. Issue 3 (July 2017) - Goyanes, Álvaro
Alvaro has more than 10 years' experience in Pharmaceutics spanning Industry and Academia. Passionate about technology and health, he is one of the first researchers investigating the opportunities for 3D printing using fused deposition modeling (FDM) for manufacturing oral dosage forms and medical devices. He is Co-Founder and Development Director at FabRx, a specialist biotech company, focused on developing 3D printing technology for fabrication pharmaceuticals and medical devices. Before moving to FabRx, he was a Postdoctoral Researcher at University College London – School of Pharmacy, manufacturing 3D printed medicines for oral drug delivery. His role included leading a formulation development project for Cycle Pharmaceuticals and managing research projects of MSc and PhD students. Prior to this, he obtained a fellowship from the Fundación Alfonso Martín Escudero to research oral colon-specific delivery of vaccines at University College London – School of Pharmacy. Here he evaluated different approaches and technologies for colonic drug delivery through conventional methods and optimized biorelevant pharmaceutical dissolution testing. Alvaro holds a PhD in Pharmaceutics from the University of Santiago de Compostela (Spain) based on pelletization by extrusion-spheronization, and a degree in Pharmacy from the same university.